A new species of mammalian trypanosome, Trypanosoma (Megatrypanum) bubalisi sp. nov., found in the freshwater leech Hirudinaria manillensis. Issue 4 (March 2022) - Su, Bi-Xiu; Wang, Ju-Feng; Yang, Ting-Bao; Hide, Geoff; Lai, De-Hua; Lun, Zhao-Rong
Graphical abstract: Highlights: The trypanosomes isolated from a freshwater leech, Hirudinaria manillensis, belong to a new species. This trypanosome is a new TthIII phylogenetic lineage in the Trypanosoma ( Megatrypanum ) clade. Water buffalo is most likely the mammalian host of this trypanosome. Results highlight the potential role of freshwater leeches in the transmission of mammalian trypanosomes. Abstract: Leeches have long been considered potential vectors for the aquatic lineage of trypanosomes, while bloodsucking insects are generally considered as the vectors for the terrestrial lineage of trypanosomes. The freshwater leech, Hirudinaria manillensis, is a widely distributed species in southern China and could potentially act as the vector for trypanosomes. Prior to this study, no trypanosomes had been reported from this leech. However, in this study, leeches were collected from three different places in Guangdong province, China, and a large number of flagellates were isolated and successfully cultured in vitro. Based on morphology, these flagellates looked like a typical trypanosome species. Analysis was carried out on the molecular sequences of the 18S rRNA gene and the glycosomal glyceraldehyde-3-phosphate dehydrogenase ( gGAPDH ) gene. To our surprise, these flagellates were identified as likely to be a mammalian trypanosome belonging to the clade containing Trypanosoma ( Megatrypanum ) theileri but they are significantly different from the typical TthI and TthII stocks. Analyses of blood composition indicated that the source of the blood meal in these leeches was from the water buffalo ( Bubalus bubalis ). To further test if this flagellate from the freshwater leech was indeed a mammalian trypanosome, we transferred the trypanosomes cultured at 27–37 °C and they were able to successfully adapt to this mammalian body temperature, providing further supporting evidence. Due to the significant genetic differences from other related trypanosomes in the subgenus Megatrypanum, we propose that this flagellate, isolated from H. manillensis, is a new species and have named it Trypanosoma bubalisi . Our results indicate that freshwater leeches may be a potential vector of this new mammalian trypanosome.